2016
DOI: 10.1136/annrheumdis-2016-209454
|View full text |Cite
|
Sign up to set email alerts
|

A20 inhibition of STAT1 expression in myeloid cells: a novel endogenous regulatory mechanism preventing development of enthesitis

Abstract: Our data reveal an important and novel interplay between myeloid cells and tissue resident cells at entheseal sites that is regulated by A20. In the absence of A20, STAT1 but not STAT3 expression is enhanced leading to STAT1-dependent inflammation. Therefore, A20 acts as a novel endogenous regulator of STAT1 that prevents onset of enthesitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 27 publications
4
52
0
2
Order By: Relevance
“…Finally, we performed therapeutic dosing experiments with treatment starting at 4 weeks, when arthritis is fulminant ( Figure 2F). For this set of experiments, we included tofacitinib as a control, at a dose commonly reported in the literature (35). There was a reduction in clinical scoring with NDI-031407 treatment, albeit predictably not as strong as in those with tofacitinib treatment.…”
Section: Ndi-031407 Controls Type 3 Immune Cell Activity With Systemimentioning
confidence: 99%
“…Finally, we performed therapeutic dosing experiments with treatment starting at 4 weeks, when arthritis is fulminant ( Figure 2F). For this set of experiments, we included tofacitinib as a control, at a dose commonly reported in the literature (35). There was a reduction in clinical scoring with NDI-031407 treatment, albeit predictably not as strong as in those with tofacitinib treatment.…”
Section: Ndi-031407 Controls Type 3 Immune Cell Activity With Systemimentioning
confidence: 99%
“…Prior psoriasis studies on markers of local inflammation which are associated with an increased risk of CVD include myeloperoxidase, a pro-inflammatory heme protein released by myeloid cells (most likely released into circulation by MPO-producing skin-infiltrating myeloid cells), and resistin, an adipose-tissue derived hormone (most likely from adipose tissue subjacent to psoriasis plaques) [21][22][23][24][25]. In addition, we and others demonstrated that myeloid cells are altered in psoriasis patients, where the number of monocyte-derived suppressor cells (MDSCs) and intermediate (CD14 + CD16 + ) monocytes are increased in psoriasis patients, potentially as a result of similarly disordered myeloid cell release [24,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of JAK1 and JAK3 kinase activity by the clinically applied JAK inhibitor tofacitinib prevented IL-17A expression in anti-TNF-treated eff Treg, suggesting that TNFα signaling is involved in driving JAK/STAT signaling. Although TNFα is not a prototypic JAK/STAT activating cytokine, the anti-inflammatory molecule A20 (encoded by TNFAIP3) that is a downstream target of TNFα signaling acts as a regulator of STAT (67,68). The absence of A20 in myeloid cells resulted in enhanced STAT1dependent inflammation (68).…”
Section: Discussionmentioning
confidence: 99%
“…Although TNFα is not a prototypic JAK/STAT activating cytokine, the anti-inflammatory molecule A20 (encoded by TNFAIP3) that is a downstream target of TNFα signaling acts as a regulator of STAT (67,68). The absence of A20 in myeloid cells resulted in enhanced STAT1dependent inflammation (68). This relationship needs to be confirmed in eff Treg.…”
Section: Discussionmentioning
confidence: 99%